Exploring fear of COVID-19 and its correlates among older adults in Bangladesh - Sabuj Kanti Mistry; A. R. M. Mehrab Ali; Farhana Akther; Uday Narayan Yadav; Mark F. Harris (Globalization and Health, 2021)
Abstract Objective This study was aimed to assess the perceived fear of COVID-19 and its associated factors among older adults in Bangladesh. Methods This cross-sectional study was conducted in October 2020 among 1032 older Bangladeshi adults aged ≥60 years. A semi-structured questionnaire was used to collect information on participants’ characteristics and COVID-19 related information. Perceived fear of COVID-19 was measured using the seven-item Fear of COVID-19 Scale (FCV-19S), where the cumulative score ranged from 7 to 35. Multiple linear regression was performed to identify factors associated with perceived fear of COVID-19. Results The mean fear score was 19.4. Participants who were concerned about COVID-19 (β: 2.75, 95% CI: 1.71 to 3.78) and overwhelmed by COVID-19 (β: 3.31, 95% CI: 2.33 to 4.29) were significantly more likely to be fearful of COVID-19. Moreover, older adults who felt themselves isolated from others and whose close friends and family members were diagnosed with COVID-19 were more fearful. However, the participants who received COVID-19 related information from the health workers had a lower level of fear (β: -1.90, 95% CI: − 3.06 to − 0.73). Conclusions The presence of overwhelming fear of COVID-19 among the older adults of Bangladesh underlines the psychological needs of these vulnerable groups. Health workers have a key role in addressing these needs and further research is needed to identify the effective strategies for them to use.